2022
DOI: 10.1038/s41416-022-01954-9
|View full text |Cite
|
Sign up to set email alerts
|

HPV self-sampling among long-term non-attenders to cervical cancer screening in Norway: a pragmatic randomised controlled trial

Abstract: Background Cervical cancer screening participation is suboptimal in most settings. We assessed whether human papillomavirus (HPV) self-sampling may increase screening participation among long-term non-attenders in Norway. Methods A pragmatic randomised controlled trial with participation as the primary outcome was initiated in the national cervical screening programme in March 2019. A random sample of 6000 women aged 35–69 years who had not attended screen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
0
21
0
3
Order By: Relevance
“…[ 12 13 14 15 ] Drawing from this information, several European nations have already incorporated the utilization of self-sampling kits into their strategies to enhance the coverage of screening programs. [ 13 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 13 14 15 ] Drawing from this information, several European nations have already incorporated the utilization of self-sampling kits into their strategies to enhance the coverage of screening programs. [ 13 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that 79.5% and 63.2% of participants who were unscreened for 4 and 10 years, respectively, who agreed to opt-in HPV self-sampling returned the kit, with respective return rates of 20.7% and 8.15% [ 26 , 27 ]. In a report from Norway, the participation rates with reminders to attend regular screening, opt-in HPV self-sampling, and opt-out HPV self-sampling were 4.8%, 17.0%, and 27.7%, respectively [ 45 ]. In the present study, opt-in HPV self-sampling had a good return rate, as in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…An additional trial of underscreened individuals in Norway evaluated opt-in and mail-to-all (with 1 reminder call) groups. Screening was increased by 12.3% over usual care for participants randomized to the opt-in group, but direct mail increased screening by 22.9% . We did not evaluate an opt-in group among overdue participants because international trial data supported direct-mail superiority .…”
Section: Discussionmentioning
confidence: 99%
“…Results may not generalize to non–English-speaking individuals or those without health insurance. The opt-in participants did not receive postinvitation reminders, but some data suggest that reminders boost opt-in effectiveness . Finally, STEP launched during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%